What do T cells see in SARS-CoV2? - Gustiananda, Marsia (Indonesia International Institute for Life Sciences, 2020)
The current epidemic caused by a novel coronavirus SARS-CoV2 as well as two previously documented pandemic caused by SARS-CoV and MERS-CoV imposes that a spillover of an animal coronavirus to humans is a continuous threat. The zoonotic nature of the infection contributes to the unpredictability of the pandemic. In such situations, the availability of the ‘off the shelf’ vaccines that target the conserved region of the coronavirus might help in preventing the spread of the diseases. Therefore, efforts to generate such vaccines should be considered as a priority. The whole genome of SARS-CoV2 is readily available in the public database one month after the first case was identified. The platform technology known as the “genome to vaccine” approach would provide useful start to identify parts of the virus proteome which can be the candidate for vaccine components. This study used an immunoinformatic approach to identify T cell epitopes from SARS-CoV2 ORF1ab polyprotein in an attempt to design a genome-derived epitope-based universal coronavirus vaccine.